PENGARUH PEMBERIAN SUNGKUP PLASTIK DAN MULSA TERHADAP DINAMIKA KADAR AIR, SUHU TANAH DAN PRODUKSI BAWANG MERAH (Allium ascalonicum L.) PADA TANAH BERIRIGASI TEKNIS - Frans Yunus; Uswah Hasanah; Muhammad Anshar (Agroland: Jurnal Ilmu-ilmu Pertanian, 2015)
This research aimed to determine the microenvironment modification techniques suited to Palu Valley shallot variety cultivated at a technical irrigated rice land. The research was located in the village of Maku, District Dolo, Sigi Regency, Central Sulawesi Province and conducted during June to November 2013. This research used a split plot design which plastic cover as the main plot consisted of no plastic cover and plastic cover. The subplot was mulch application consisted of no mulch application, black plastic, silver plastic, and rice straw mulch. Each treatment was replicated 3 times. Higher shallot dry weight was found in the application of the rice straw mulch at 20 days after planting and at harvesting time.  The plastic cover produced larger tuber fresh weights of shallots than that with no plastic cover. It also increased the soil water content at day three and four as well as soil temperature at 16:00 to 17:00 p.m. The only significant interaction effect was on soil temperature which was lowest when no plastic cover combined with the black plastic mulch.Key words : Mulch, plastic cover, shallots.